OPTIMASI PROSES PCR PADA PLB TANAMAN ANGGREK ONCIDIUM HASIL PERLAKUAN PENETESAN MUTAGEN KIMIA COLCINE - Agus Zainuddin (Jurnal Gamma, 2006)
This research is aim to study the PCR optimization using primer of random Amplified polymorphie DNA (RAPD) of Oncidium sp. PLB which have been treated with conditation of colchicine concentration 0%; 0.01%;0.03%;0.05%;0.07% and 0.09%.Through process of PCR RAPD DNA of Oncidium PLB that previously given treatment of drop colchicine 0% until 0.09% have secceeded to be obtained the ribbons of DNA orchid genomic resulth. Penulis adalah MAhasiswa Jurusan Agronomi Fakultas Pertanian Universitas Muhammadiyah Malang